Meta-Analysis in Measuring the Effectiveness of Problem-Based Learning Models in Vocational Education - Rosi Yulianti; Asmar Yulastri; Ambiyar; M Giatman (AI Society & STMIK Indonesia, 2023)
Introduction to learning models is key to discussing the approaches used to transfer knowledge and skills to students. Learning models encompass various strategies and approaches designed to create an effective learning environment and stimulate intellectual and social development, particularly in vocational education. Therefore, this research will explore the effectiveness of one learning model in vocational education, namely Problem-Based Learning (PBL). This study implements the meta-analysis method by synthesizing data from 15 research articles from 2019 to 2023. Using secondary data from Classroom Action Research (CAR) studies, this research calculates the effect size to determine the impact of the PBL model on learning outcomes. The results, presented graphically, show a significant effect size (1.02), indicating a very high impact of the PBL model in vocational education. The discussion emphasizes factors contributing to this effectiveness, including a focus on student autonomy, the development of soft skills, and alignment with the demands of the vocational workforce. Overall, the PBL model emerges as a highly effective approach in improving learning outcomes and preparing vocational education students for real-world challenges